Memahami Konsep Ajaran Doketisme - Albertus O. Boimau; Aben T. Banamtuan; Mozes Lawalata (Jurnal Pendidikan Agama dan Teologi, 2024)
Docetism is a term that states that Jesus Christ was not truly human, but only appeared to be human. This word comes from the Greek "dokein" which means "to appear or appear. Docetism makes the human Jesus only an ethereal creature, an illusion that appears real to humans but actually never existed. The theory of Docetism comes from Gnosticism, which says that this was a dangerous and greatest teaching for the Church that was popular in the first to the end of the second century AD. In the Gospel of John, Docetism is a theological view that teaches that Jesus Christ only had an illusion or pseudo-human existence. According to John's Christology, it strongly opposes docetism in the letter of 1 John in the Bible, which asserts that Jesus Christ came in true flesh and not just in an illusory form. John emphasized the importance of Jesus' physical existence as the "FOUNDATION" for the Christian Faith.